Linkage of Financial Wellbeing and Mental Health among Private College Teachers - Panta, Mahima; Bhusal, Navraj; K C, Sriya (Chaturbhujeshwar Academic Journal, 2025)
Mental health issues are prevalent among the teaching fraternity and are often associated with financial wellbeing (FWB). This study investigates the relationship between FWB and mental health in the Nepalese context, focusing on private college teachers in the Kathmandu Valley. Data were collected from 128 teachers using the Multidimensional Subjective Financial Well-Being Scale (MSFWBS) and the Depression Anxiety Stress Scale (DASS-21) under a cross-sectional research design with a deductive approach. Descriptive statistics, correlation, and hierarchical regression analyses were employed to assess the status and associations of financial wellbeing and mental health. Findings indicate a moderate level of mental health problems among the teachers and a significant negative correlation between FWB components and mental health issues. Among the FWB factors—general subjective FWB, financial future, money management, having money, and peer comparison—peer comparison emerged as the strongest predictor. The study presents a foundational framework linking FWB components to mental health outcomes in private college teachers and highlights the need for effective financial support mechanisms to mitigate mental health challenges in this group.